Systemic and regional hemodynamic effects of calcitonin gene-related peptide. - Donald J. DiPette; Kathy Schwarzenberger; Newcastle Kerr; O. B. Holland (1987)
Calcitonin gene-related peptide, a 37-amino-acid neuropeptide, has been shown to be widely distributed in periadventitial nerves throughout the cardiovascular system, particularly in association with coronary arteries. In vivo and in vitro studies have demonstrated that calcitonin gene-related peptide possesses potent vasodilator properties. Circulating calcitonin gene-related peptide is derived primarily from periadventitial nerves, though its systemic and regional hemodynamic effects are unknown. In this study, systemic and regional hemodynamics were determined by the radioactive microsphere technique prior to and following the intravenous administration of 65-pmol and 2.2-nmol doses of calcitonin gene-related peptide and vehicle to three groups of conscious, unrestrained rats. Vehicle administration did not change any systemic or regional organ hemodynamic parameter determined. In contrast, 65 pmol and 2.2 nmol of calcitonin gene-related peptide significantly decreased mean blood pressure and total peripheral resistance and increased heart rate in a dose-dependent manner, while only slightly increasing cardiac output. Both 65-pmol and 2.2-nmol doses of calcitonin gene-related peptide significantly increased blood flow (percentage of cardiac output) to the heart. There was no difference in blood flow to the heart between the two doses. In addition, the 2.2-nmol dose of calcitonin gene-related peptide significantly increased blood flow to the stomach, liver, and skin and decreased it to the brain, kidneys, and spleen. In conclusion, calcitonin gene-related peptide infusion decreases blood pressure in a dose-dependent manner primarily by peripheral vasodilation. In addition, calcitonin gene-related peptide selectively changes regional organ blood flow, particularly to cause coronary vasodilation.(ABSTRACT TRUNCATED AT 250 WORDS)